Cardiac rehabilitation - D Nieman (AOSIS, 1981)
In the Republic of South Africa, ischaemic heart disease is the main cause of death amongst Whites in the age group 20 - 65 years. The percentage for ischaemic heart disease of all deaths from diseases of the circulatory system for Whites in the age group 25 - 34 is 63% for males and 21% for females. In the age group 35 - 44 the percentages are 77% for males and 34% for females (22, p.1025).